2015
DOI: 10.1097/md.0000000000001874
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Treatment of Extremity Chronic Osteomyelitis in Southern China

Abstract: Although extremity chronic osteomyelitis is common in China, updated data were still limited regarding its characterizations. The present study aimed to review clinical features of extremity chronic osteomyelitis in Southern China.A retrospective analysis was conducted in the patients who had sought medical attention from January 2010 to April 2015 for extremity chronic osteomyelitis in Nanfang Hospital in Southern China. Clinical data were collected and analyzed.A total of 394 patients (307 males and 87 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
82
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 31 publications
10
82
5
2
Order By: Relevance
“…In our study, osteomyelitis cases were more common in males (76%) as compared to females (24%) with a male: female ratio of 3.16:1. Similar results were reported by Kumar A et al [8] , Jiang N et al [9] and Singh A et al [10] who showed male: female ratio to be 2.72:1, 3.53:1 and 2.7:1 respectively. In the current study, the most common predisposing factor leading to osteomyelitis was trauma due to road side accidents accounting for 45% cases followed by post-operative infections (21%), orthopaedic implants (17%), haematogenous (11%), diabetes mellitus (4%) and others.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, osteomyelitis cases were more common in males (76%) as compared to females (24%) with a male: female ratio of 3.16:1. Similar results were reported by Kumar A et al [8] , Jiang N et al [9] and Singh A et al [10] who showed male: female ratio to be 2.72:1, 3.53:1 and 2.7:1 respectively. In the current study, the most common predisposing factor leading to osteomyelitis was trauma due to road side accidents accounting for 45% cases followed by post-operative infections (21%), orthopaedic implants (17%), haematogenous (11%), diabetes mellitus (4%) and others.…”
Section: Discussionsupporting
confidence: 80%
“…Contamination by a myriad of pathogenic Gram-negative bacteria is not only found in open fractures, but in recent studies involving trauma centers of developing countries, P. aeruginosa has been increasingly identified as the causative organism in secondary hospital-acquired osteomyelitis and implant-associated infections [4, 6, 8, 31, 32]. In this study, P. aeruginosa accounted for the second most common isolated bacteria on patients with PTO and was strongly associated with recurrent infections in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a Chinese cohort study addressing the epidemiology of COM confirmed its rising frequency, especially among previously healthy young adults involved in road traffic accidents and interpersonal violence [8]. The combination of prompt diagnosis, aggressive surgical debridement, and targeted administration of antibiotics may help reduce the growing frequency of PTO, especially among populations in the developing world [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8] reports that in southwest China, the top two infection sites are tibia (57.5%) and femur (26.8%). Jiang et al [9] reported a similar result for southern China, finding the most frequent single infection site was the tibia (39.00%), followed by the femur (24.46%), and calcaneus (11.46%). One possible reason for this difference between north and south China could be the dense population found in southern China, leading to more frequent road and industrial accidents.…”
Section: Discussionmentioning
confidence: 69%
“…It also poses great challenges for orthopedists [7]. Wang [8] and Jiang et al [9] provide recent data on the epidemiology of chronic osteomyelitis in southwest and southern China, which can be used by local government policy-makers and by clinicians. However, China is a country of great diversity in its population, climate and culture.…”
mentioning
confidence: 99%